2022-RA-1101-ESGO Prediction of incomplete cytoreduction in primary debulking surgery of advanced stage ovarian cancer patients: Usefulness of the entire peritoneal cancer index (PCI) versus exclusive assessment of small intestine/mesentery/hepatoduodenal ligament carcinosis. (20th October 2022) - Goerdt, Clara E; Bokhua, Davit; Auletta, Valentina; Kather, Angela; Runnebaum, Ingo B
Abstract : Introduction/Background: Complete cytoreductive surgery (CRS) at primary debulking surgery in advanced stage ovarian cancer is a strong prognostic factor. Extent of peritoneal carcinosis, scorable by peritoneal cancer index (PCI), is critical for CRS success. In our cohort, we aimed to evaluate predictive power of PCI compared to sole consideration of carcinosis in small intestine, mesentery and hepatoduodenal ligament (CaIMHL). Methodology: Monocentric retrospective study at a tertiary care university hospital center with 795 invasive OC cases 2006 until 2020. Since 2014, PCI was routinely documented preceding debulking surgery. Inclusion criteria: stage FIGO III/IV disease and primary surgery using maximum effort with intention of complete CRS. Results: 116 patients had complete documentation of PCI and CRS. Median PCI was 20.5 (range, 2–36). CRS was successful (completeness of cytoreduction [CC]0, no residual macroscopic tumor) in 89 patients (76.5%). In these patients, PCI was significantly lower (median PCI 18, range 2–36, p = <0.001) compared to patients with residual tumor (CC1–3, median PCI 25, range 17–34). ROC analysis for PCI as predictor for residual tumor revealed an AUC of 0.855 (95% CI, 0.784–0.927). Cutoff PCI values of 16 and 24 predicted residual tumor with a sensitivity of 100% resp. 63.0%, and a specificity of 46.1% resp. 85.4%. Risk for residual tumor was increased with each point of PCI by 28.6% (OR 1.286, 95% CI, 1.153 to 1.434, p = <0.001) and a PCI > 24 increased the risk almost 10 fold (OR 9.938, 95% CI, 3.738 to 26.423, p = <0.001). Presence of CaIMHL increased the risk 3.304 fold without statistical significance (OR 3.304, 95% CI, 0.716 to 15.249, p = 0.126). Conclusion: Scoring of PCI had higher predictive power for residual tumor than presence of CaIMHL. PCI > 24 indicates high risk for residual tumor. These patients may benefit from interval debulking surgery.